The Role of Interlayer Chemistry in Li‐Metal Growth through a Garnet‐Type Solid Electrolyte. Issue 12 (12th February 2020) - Kim, Sewon; Jung, Changhoon; Kim, Hyunseok; Thomas‐Alyea, Karen E.; Yoon, Gabin; Kim, Byunghoon; Badding, Michael E.; Song, Zhen; Chang, JaeMyung; Kim, Jusik; Im, Dongmin; Kang, Kisuk
Abstract: Securing the chemical and physical stabilities of electrode/solid‐electrolyte interfaces is crucial for the use of solid electrolytes in all‐solid‐state batteries. Directly probing these interfaces during electrochemical reactions would significantly enrich the mechanistic understanding and inspire potential solutions for their regulation. Herein, the electrochemistry of the lithium/Li7 La3 Zr2 O12 ‐electrolyte interface is elucidated by probing lithium deposition through the electrolyte in an anode‐free solid‐state battery in real time. Lithium plating is strongly affected by the geometry of the garnet‐type Li7 La3 Zr2 O12 (LLZO) surface, where nonuniform/filamentary growth is triggered particularly at morphological defects. More importantly, lithium‐growth behavior significantly changes when the LLZO surface is modified with an artificial interlayer to produce regulated lithium depositions. It is shown that lithium‐growth kinetics critically depend on the nature of the interlayer species, leading to distinct lithium‐deposition morphologies. Subsequently, the dynamic role of the interlayer in battery operation is discussed as a buffer and seed layer for lithium redistribution and precipitation, respectively, in tailoring lithium deposition. These findings broaden the understanding of the electrochemical lithium‐plating process at the solid‐electrolyte/lithium interface, highlight the importance of exploring various interlayers as a new avenue for regulating the lithium‐metal anode, and also offer insight into the nature of lithium growth in anode‐free solid‐state batteries. Abstract : The work presented here shows that lithium growth can effectively be tailored by exploiting interlayer chemistry on a solid electrolyte, which can be directly probed by real‐time observation of lithium in an anode‐free solid‐state battery. With these observations, a dynamic role for the interlayer, during battery operation, is proposed: it acts as a buffer layer for lithium redistribution and a matrix for lithium precipitation.